Quality Service of Building and Land Tax Services at Revenue Agency of Polewali Mandar Regency - Taufiq, Muhammad Syihabuddin; Saputra, Aco Nata; Pahruddin; Husnia (MultiTech Publisher, 2024)
The problem studied in this research is the service quality of bureaucratic officials seen from the aspects of convenience, clarity, and certainty, security, openness of information, fairness, speed,economy, the efficiency of Building and Land Tax Services in Polewali Mandar regency. This research is descriptive research that uses a quantitative approach with survey methods. In this research, the data collection technique used is a questionnaire, i.e. collecting data using a list of questions and observation, i.e. direct observation of objects. The research results show that services measured based on indicators of simplicity, clarity and certainty, security, efficiency, justice, information openness, and economy in PBB services from the Regional Revenue Agency of Polewali Mandar Regency are very good. This is evident from the indicator score range of 3.15 to 3.42, which shows that the UN bureaucracy is in the good – very good category. Meanwhile, the Polman Regional Revenue Agency's PBB service speed indicator is classified as low with a score of 2.98. not satisfying the community, particularly about time constraints. Long bureaucratic procedures are one of the things that slow down service, this problem still needs to be resolved by government officials at the Polman Regional Revenue Agency.